TINJAUAN YURIDIS NFT (NON-FUNGIBLE TOKEN) SEBAGAI HAK CIPTA DI INDONESIA - NIM. A1011211262, MOHAMMAD ZACKY (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractNon-fungible tokens (NFTs) have emerged as a global phenomenon, attracting the attention of diverse groups, including artists, collectors, and investors. In Indonesia, the subject of NFTs has gained significant public attention when individuals achieve financial gains through the sale of NFTs. However, the Indonesian government faces challenges in regulating NFTs (Non-Fungible Tokens), particularly in terms of their categorization within copyright law and the establishment of legal protection under Indonesian legislation. The objective of this study is to elucidate the categorization of NFTs (Non-Fungible Tokens) within the context of copyright law and to furnish an overview of the legal protection available for NFTs (Non-Fungible Tokens) in accordance with legislation that accommodates them. This research employs normative research methods, which entail examination of library materials and secondary data to ascertain answers to the research questions. The objective of this normative research is to provide juridical arguments related to the existence of a legal vacuum, vagueness, and conflict of norms in this case regarding the categorization of NFTs (Non-Fungible Tokens) as copyrights and their legal protection according to applicable laws and regulations in Indonesia. In this study, NFTs (Non-Fungible Tokens) can be categorized as intellectual property rights and included in copyright, which is the object of digital works. In terms of legal protection, NFTs (Non-Fungible Tokens) have been recognized as a form of copyright protection. Furthermore, Indonesian law, particularly the Copyright Act and the Information and Electronic Transactions Act, provides a legal foundation for safeguarding digital assets, including NFTs. However, as technology evolves, the legal framework must continuously adapt to address emerging issues such as ownership disputes, unauthorized duplication, and fraudulent transactions. Therefore, it is essential for policymakers to establish clearer and more comprehensive regulations to ensure that NFTs (Non-Fungible Tokens) are effectively protected under Indonesian law while maintaining legal certainty for stakeholders. Keywords: Copyright; Digital Assets; Indonesian law; Law Protection; NFTs; RegulationAbstrak NFT (Non-Fungible Token) adalah aset digital yang menjadi fenomena global bagi berbagai kalangan, termasuk seniman, kolektor, dan investor. Di Indonesia, NFT (Non-Fungible Token) menjadi perbincangan ketika seseorang mendapatkan keuntungan dari menjual NFT. Namun, hal ini menjadi tantangan tersendiri bagi pemerintah Indonesia dalam mengatur NFT (Non-Fungible Token), terutama dalam hal pengkategorian NFT (Non-Fungible Token) dalam hak cipta serta bagaimana perlindungan hukum dalam peraturan perundang-undangan di Indonesia. Tujuan dari penelitian ini adalah untuk memberikan kejelasan terkait pengkategorian NFT (Non-Fungible Token) dalam hak cipta serta memberikan gambaran mengenai perlindungan hukum berdasarkan peraturan perundang-undangan yang mengakomodir NFT (Non-Fungible Token). Penelitian ini menggunakan metode penelitian normatif, yang meneliti bahan pustaka dan data sekunder untuk mencari jawaban dari penelitian ini. Penelitian normatif dimaksudkan untuk memberikan argumentasi yuridis terkait adanya kekosongan hukum, kekaburan, dan konflik norma dalam hal ini mengenai pengkategorian NFT (Non-Fungible Token) sebagai hak cipta serta perlindungan hukumnya menurut peraturan perundang-undangan yang berlaku di Indonesia. Dalam penelitian ini, NFT (Non-Fungible Token) dapat dikategorikan sebagai hak kekayaan intelektual dan termasuk dalam hak cipta yang merupakan objek karya digital. Dalam perlindungan hukumnya sendiri, NFT (Non-Fungible Token) telah mendapatkan perlindungan hukum menurut peraturan perundang-undangan di Indonesia, antara lain Undang-Undang Hak Cipta yang mengatur hak dan kewajiban suatu karya hak cipta, serta Undang-Undang Informasi dan Transaksi Elektronik yang melindungi terhadap upaya pengambilan karya NFT secara melawan hukum. Selain itu, penting untuk mempertimbangkan mekanisme penyelesaian sengketa yang mungkin saja timbul akibat pelanggaran hak cipta NFT serta perlunya regulasi yang lebih spesifik agar NFT dapat diakomodasi dengan baik dalam sistem hukum Indonesia. Dengan perkembangan teknologi yang pesat, diperlukan kebijakan yang fleksibel namun tetap memberikan kepastian hukum bagi para pemilik NFT. Kesadaran akan hak dan kewajiban dalam kepemilikan NFT juga perlu ditingkatkan agar ekosistem digital yang sehat dan berkelanjutan dapat terbentuk, sehingga mampu memberikan manfaat optimal bagi para pemangku kepentingan di Indonesia. Kata Kunci: Aset Digital; Hak Cipta; Hukum Indonesia; NFT; Perlindungan Hukum; Regulasi